Self-efficacy, social activity, and spirituality in the care of elderly patients with polypharmacy in Germany: a multicentric cross-sectional study within the HoPES3 trial - Sturm, Noemi; Stolz, Regina; Schalhorn, Friederike; Valentini, Jan; Krisam, Johannes; Frick, Eckhard; Mächler, Ruth; Szecsenyi, Joachim; Straßner, Cornelia (Healthcare, 2021)
About one third of Europe’s elderly population takes ≥5 drugs. Polypharmacy increases their risk of adverse drug reactions. To ensure drug safety, innovative approaches are needed. The aim of this cross-sectional study was to explore the relationship between psychosocial factors and medication-related beliefs and behaviors. Medication lists of 297 patients were recorded according to the ATC classification. Correlations between the dependent variables, Medication Adherence (MARS) and Beliefs about Medicines (BMQ), and independent variables, General Self-Efficacy (GSE), self-efficacy for managing chronic diseases (SES6G), spiritual needs (SpNQ), patient activity (PAM), loneliness (DJG), and social networks (LSNS), were measured. Patients with higher self-efficacy (OR: 1.113; 95% CI [1.056-1.174]; p < 0.001) or self-confidence in managing their chronic condition (OR: 1.188; 95% CI [1.048-1.346]; p < 0.007) also showed higher adherence. Lonely patients (OR: 0.420; 95% CI [0.267-0.660]; p < 0.001) and those with a need for inner peace (OR: 0.613; 95% CI [0.444-0.846], p = 0.003) were more likely nonadherent. Stronger positive beliefs about medications’ usefulness weakly correlated with higher scores on the SES6G (ρ = 0.178, p = 0.003) and GSES scale (ρ = 0.121, p = 0.042), patient activity (ρ = 0.155, p = 0.010) and functioning social networks scale (ρ = 0.159, p = 0.008). A weak positive correlation was found between loneliness and the belief that drugs were harmful (ρ = 0.194, p = 0.001). Furthermore, interesting correlations were detected regarding the number of medications and overuse beliefs. Psychosocial factors, such as self-efficacy, loneliness, and spiritual needs and medication-related beliefs and behaviors seem to interrelate. Addressing these factors may improve medication management and drug safety.